Knowledge, Attitude and Significance of Sex Education AmongStudents of the University of Nigeria Secondary School,Enugu Campus, Nigeria - Kizito, Okafor Oluchi; Okafor, Ani Celestine; Sunday, Onah Emmanuel; Ifebuchechukwu, Ugwu Valentine; Florentina , Anikpo Eberechukwu (International Journal of Rehabilitation and Special Education (IJRSE), 2023)
Sex health is an essential part of adolescent development. Sex education is important to provide information on body development. Sexually transmitted diseases and its prevention. This study aimed at determining the knowledge, attitude and significance of sex education among secondary school students in University of Nigeria secondary school Enugu campus, Nigeria: This study was a cross sectional study which involved a total of 368 students of University of Nigeria secondary school Enugu campus that were issued a questionnaire between the age bracket 20-22 the largest percentage of respondents, 58.2% (214) are those within the age of 13-15 years. Majority were males and these constituted about 240 (67.9%). The classes had equal sizes of 184(50%) each. Majority, 363 (98.6%) were Igbo’s and about 365 (99.2%) were Christians. Majority of respondents, 261(70.9%) had knowledge of sex education. Most of the respondents 163 (30.7%) agreed their source was from school. The rest 69.3% heard from other sources. On sex education, majority 24(145%) said it was all about teaching various topics on sex education. Many participants, 220 (59.8%) did not know the types of sex education. Only 148 (40.2%) agreed to knowing the types. On the types, majority 76(20.7%) agreed to comprehensive sex education types. Majority of participants, 235 had not attended sex education program in the past. Out of those who had attended, 64.7% had done so only once. Majority 267 (72.6%) agreed that sex education was not given much attention in secondary school. 329 (89.4%)